1992
DOI: 10.1139/v92-367
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopic study of the interaction of metal ions with diethyl phosphate, a model for biological systems

Abstract: JANUSZ STANGRET and RODRIGUE SAVOIE. Can. J. Chem. 70, 2875Chem. 70, (1992. We have studied, using Raman and infrared spectroscopy, the interaction of various monovalent, divalent, and trivalent metal cations with the PO, group of diethyl phosphate in aqueous solution, at meta1:phosphate ratios ranging from 1 :40 to 6 : 1. The results show that the metal cations interact with the phosphate groups in various ways and to different extents. Spectral characteristics for some specific types of interactions are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
45
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 16 publications
(25 reference statements)
13
45
1
Order By: Relevance
“…The strength of this shift correlates with the MOO(a) distance and the type of binding mode. Experimentally, such a shift in the ssPAO vibration was observed for samples of diethyl phosphate containing Ca 2ϩ ions, but not for those with Ni 2ϩ ions [13]. In the present study, the theoretical calculations predicted a similar effect for the inner-sphere complexes of Ca 2ϩ and Mg 2ϩ .…”
Section: ؉ ) Complexessupporting
confidence: 62%
See 3 more Smart Citations
“…The strength of this shift correlates with the MOO(a) distance and the type of binding mode. Experimentally, such a shift in the ssPAO vibration was observed for samples of diethyl phosphate containing Ca 2ϩ ions, but not for those with Ni 2ϩ ions [13]. In the present study, the theoretical calculations predicted a similar effect for the inner-sphere complexes of Ca 2ϩ and Mg 2ϩ .…”
Section: ؉ ) Complexessupporting
confidence: 62%
“…It has been observed that the presence of Ni 2ϩ and Ca 2ϩ leads to slight red shifts in the frequencies of diethyl phosphate [13]. Another noteworthy observation stemming from these experimental data is that the intensity of these peaks increases, becoming larger than that attributable to the ssPAO vibration.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…By contrast, indications are that the shift of cAMP's ν s (PO 2 − ) mode in the H II phase of aqueous MO/DOPC mixture (see Table I) is related to the electrostatic interaction. For example, the studies of dialkylphosphates have demonstrated a decrease of the ν s (PO 2 − ) mode frequency upon formation of the PO 2 − • • •HOH hydrogen bond [19,20], and the effect becomes even more pronounced (further 3-5-cm −1 downshift) by the additional interaction with cations [21].…”
Section: Raman Spectroscopy Of the Aqueous Mo/dopc Liquid-crystallinementioning
confidence: 99%